PERAN PENDETA SEBAGAI GEMBALA JEMAAT: MELAYANI ATAU DILAYANI? - Tirza Prilly Supit; Yohan Brek (PT. Giat Konseling Nusantara, 2026)
Pastoral ministry is fundamentally rooted in the calling to serve, as exemplified by JesusChrist, the Good Shepherd. However, in today’s ecclesial context, it is not uncommon tofind situations where pastors are positioned or even positions themselves as those hoare served rather than as servants. This study aims to critically examine the role ofpastors as shepherds of the congregation amid the tension between the calling to serveand the tendency to be served. The research employs a qualitative method with apastoral case study approach by interviews, observation, and reflection on ministryexperiences within the congregation. The findings reveal a shift in the understanding ofpastoral ministry, influenced by congregational expectation, church culture, structuralworkload, and the psychological and spiritual conditions of pastors. This shif affectspastor’s relationships, the quality of shepherding, and the spirituality of ministry. Thestudy emphasizes the importance of continuous theological reflection and spiritualformation for pastors to remain faithful to their identity as servants and shepherds ofGod’s people. These findings are expected to contribute to the development of pastoraltheology and the practice of church ministry that is healthier, relational, and centered onthe example of Christ.